Atypical presentation of Rickettsial spotted fever - Prabhakar, Uday; Singh, Anup (Journal of Ayub Medical College Abbottabad, 2017)
Acute febrile illness is a common entity in tropics and often is challenging due a host of pathogenic bacteria, viruses and fungi. Extensive work up is required for better management. Rickettsiosis is uncommon and hence comes lower down in the differentials of multiorgan failure being superseded by the more common diseases as malaria, enteric fever and Dengue. We document a case of young male presenting with high grade fever, multiorgan dysfunction (hepatic, renal, neurological and respiratory involvement), conjunctival suffusion, retiform rash and without lymphadenopathy. The diagnosis was further challenging because the rashes appeared late at 8th day in the course of illness, unlike the typical disease where rashes come on early in day 3-6 of the disease. Patient responded to timely treatment with doxycycline. Thus, a high index of suspicion is needed to diagnose Rickettsiosis in geographical areas apparently free of the disease. Keywords: Rickettsia; Weil-Felix; Purpura fulminans; Multiorgan dysfunction; Rash